Analisis Tingkat Kepercayaan Diri Siswa dalam Pembelajaran Renang di SMA Negeri 1 Makassar - Ricardo V. Latuheru (Jurnal Inovasi Olahraga, 2026)
Purpose of the study: This study aims to analyze the level of student self-confidence in swimming learning at SMA Negeri 1 Makassar. Self-confidence is one of the crucial psychological aspects in aquatic learning, as many students experience anxiety and fear of water which ultimately affects their participation and learning outcomes. Materials and methods: This research uses a quantitative descriptive method with a survey approach. The research instrument used was a self-confidence questionnaire adapted from the Self-Confidence Scale developed by Schwarzer and Jerusalem (1995), which had been validated by experts with a validity value of 0.78 and reliability of 0.89. The research sample consisted of 80 students (38 male and 42 female) who were selected using a proportional random sampling technique. Data were analyzed using descriptive statistics and the t-test to see differences based on gender. Results: The results showed that the level of student self-confidence in swimming learning was in the moderate category with an average score of 68.45 (SD = 12.34). Male students had a slightly higher average score (71.23; SD = 11.87) compared to female students (65.93; SD = 12.41), and the t-test results showed a significant difference (t = 2.112; p = 0.038 < 0.05). Conclusions: The novelty of this research lies in the focus of analysis on the psychological dimension of students in the context of swimming learning at the high school level in Eastern Indonesia, an area that has received limited attention in previous studies. The findings of this study are expected to be a basis for physical education teachers in designing swimming learning strategies that pay attention to students' self-confidence factors.